EVALUATION OF LOCAL GOVERNMENT CAPACITY IN SUPPORTING SMART GOVERNMENT ASPECTS (SAMARINDA CITY CASE STUDY) - Rizky Arif Nugroho; Andi Atikah Melinda Septiana (Universitas Pancasakti Tegal, 2023)
Samarinda City, according to Samarinda Long Term Planning, was directed to be a sustainable city with a smart city as its foundation. The plan was in line with the Movement to 100 Smart Cities in Indonesia. Therefore, Samarinda City compiled Masterplan of Samarinda Smart City 2017-2002 to support the movement. The local government’s capacity to support the smart government concept had to be addressed by evaluating variables for enhancing the capacity using the scoring method. As stated in the Internal Affair Minister’s presentation on Smart City Development, the sample populations are government bodies. Regarding scoring analysis using each collected respondent response, Samarinda City scored point accounted for 2.1 meaning MEDIUM.